Effect of regular terbutaline and budesonide on bronchial reactivity to allergen challenge - Wong, C; Wahedna, I; Pavord, I; Tattersfield, A (1994)
There is a transient rebound increase in bronchial reactivity to histamine and methacholine following regular treatment with an inhaled β-agonist. We set out to determine whether the response to allergen was increased after cessation of regular inhaled terbutaline and whether concomitant inhaled budesonide modifies this response. In a double-blind, double-dummy, parallel group design we studied 41 subjects (37 evaluable) with mild asthma who were allergic to Dermatophagoides pteronyssinus, grass pollen, or cat fur. Following a 2 wk run-in period, subjects underwent a fixed three-dose allergen challenge based on their previously determined provocative concentration of allergen producing a 20% fall in FEV (PC) before starting terbutaline 1,000 μg or placebo three times daily and budesonide 800 μg or placebo twice daily for a period of 2 to 4 wk (mean 18 d). The same three-dose allergen challenge was repeated 33 h after stopping treatment. During treatment evening peak flow values were highest in the terbutaline plus budesonide group. Following regular terbutaline there was no rebound increase in bronchial reactivity to allergen. Following budesonide there was a significantly smaller response to allergen and an increased FEV compared with the other three groups, including the budesonide plus terbutaline group. The changes in median (95% CI) allergen PC after budesonide, terbutaline, budesonide plus terbutaline, and placebo were 0.79 (0.3, 2.3), 0.11 (-0.4, 0.6), 0.24 (-0.4, 0.5) and -0.47 (-1.5, 0.1) doubling doses (p < 0.01). The respective changes in mean FEV were 0.34, -0.16, - 0.01, and 0.06 L (p < 0.005). Thus bronchial reactivity to allergen was not increased after regular inhaled terbutaline. Terbutaline enhanced the effect of budesonide on peak expiratory flow (PEF) during treatment but attenuated the bronchodilatation and protection against allergen seen following budesonide alone.